BODY SHAMING IN MOVIES: A CASE STUDY ON SELECTED MOVIES - H, Harsha .; Joseph, Kelia; Devassy, Mariya; Sreena, (International Journal of Psychosocial Rehabilitation, 2020)
--This paper aims to examine the potential influence of movies, in support and reflection of body shaming among women in the society. Body shaming happens in many ways; it is criticising or judging someone’s appearance or comment on their body and comparing it to other individuals. Women are always the major victims of body shaming. Female body-shaming is discussed in movies as an important element nowadays. Females always get conscious and influenced by their body, size, and colour. It’s becoming a normal process that one fat girl or dark-skinned will get bullied by others in society. She has to be shameful about what she is. Films are considered as the reflection of society and vice-versa. It influences people’s attitude as a whole and one to others. Body shaming has different perspectives in different cultures. This research is focusing on how movies indulge with body-shaming in different ways. For instance, comparing the Indian and the American culture, one can observe that body shaming happens in a repulsive way may be with different means. This paper intends to know how female body-size, colour etc. are portrayed in films. The paper attempts to analyse two selected movies from two different cultures; Dumplin’(2018), Thamaasha(2019). It relies on the social stigma of ‘body image’ and the effects on the society where the concepts of gender, race, and sexuality play a vital role.